2020
DOI: 10.3390/s20143983
|View full text |Cite
|
Sign up to set email alerts
|

A Certificateless Aggregate Arbitrated Signature Scheme for IoT Environments

Abstract: The Internet of Things (IoT) environment consists of numerous devices. In general, IoT devices communicate with each other to exchange data, or connect to the Internet through a gateway to provide IoT services. Most IoT devices participating in the IoT service are lightweight devices, in which the existing cryptographic algorithm cannot be applied to provide security, so a more lightweight security algorithm must be applied. Cryptographic technologies to lighten and provide efficiency for IoT environments are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…In wireless and mobile networks with limited storage and computing resources, certificateless cryptography has more advantages because of its low dependence on infrastructure and short security parameters. However, while achieving low computational costs, many certificateless schemes proposed in the Internet of things environment [17][18][19][20][21][22][23] cannot simultaneously provide provable security. Kumar et al [17] claimed that their newly proposed certificateless aggregate signature scheme is secure against both types of attackers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In wireless and mobile networks with limited storage and computing resources, certificateless cryptography has more advantages because of its low dependence on infrastructure and short security parameters. However, while achieving low computational costs, many certificateless schemes proposed in the Internet of things environment [17][18][19][20][21][22][23] cannot simultaneously provide provable security. Kumar et al [17] claimed that their newly proposed certificateless aggregate signature scheme is secure against both types of attackers.…”
Section: Introductionmentioning
confidence: 99%
“…Kasyoka et al [28] showed the security vulnerabilities of Wei and Ma's [19] signcryption scheme and proposed corresponding modifications to show how their scheme could be made more secure. Xu and Zeng [29] pointed out that the certificateless aggregate arbitrated signature scheme proposed by Lee et al [22] is not secure for type-1 attackers that can replace user public keys. ey also showed that Addobea et al's [23] offline-online certificateless signature scheme cannot achieve correctness.…”
Section: Introductionmentioning
confidence: 99%
“…The authors of [ 10 ] suggest a new signature method employing certificateless public key cryptography (CL-PKC) to produce and validate a message’s signature in an IoT environment. The advanced system is a certificateless aggregate arbitrated signature, and the gateway aggregates the signatures of messages created by the device group to lessen the volume of the whole signature.…”
mentioning
confidence: 99%